2019
DOI: 10.1007/s00268-019-05194-6
|View full text |Cite
|
Sign up to set email alerts
|

Depth of Invasion into the Circular and Longitudinal Muscle Layers in T2 Esophageal Squamous Cell Carcinoma Does Not Affect Prognosis or Lymph Node Metastasis: A Multicenter Retrospective Study

Abstract: Background Although a greater depth of tumor invasion is correlated with a poorer prognosis in esophageal squamous cell carcinoma (ESCC), it remains controversial whether T2 ESCC should be subclassified by circular and longitudinal muscle invasion. We conducted a multicenter retrospective study to evaluate the relationship between the depth of invasion and long‐term outcome and to identify the clinical significance of subclassifying T2 ESCC. Methods Patients with T2 ESCC who underwent esophagectomy at two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The rate of LNM differs substantially between different T stages. In this study, the LNM rates of stage T1 and T2 were 16.4% and 36.2%, respectively, which was consistent with the reported incidence ( 10 , 35 , 37 , 44 ). To distinguish the ability of the model to discriminate LNM in patients with T1 and T2 stages, we tested the optimal model on different T stages of the external test set.…”
Section: Discussionsupporting
confidence: 91%
“…The rate of LNM differs substantially between different T stages. In this study, the LNM rates of stage T1 and T2 were 16.4% and 36.2%, respectively, which was consistent with the reported incidence ( 10 , 35 , 37 , 44 ). To distinguish the ability of the model to discriminate LNM in patients with T1 and T2 stages, we tested the optimal model on different T stages of the external test set.…”
Section: Discussionsupporting
confidence: 91%
“…These results were similar to those reported by Duan et al, 7 who also concluded that T2 substage was an independent prognostic factor from a single‐center, small sample size database (120 ESCC). In contrast, Tian et al 8 showed that the T2 substage was not significantly associated with ESCC patient survival in Cox regression analysis. Interestingly, they found that survival time was significantly different among T1b, T2 circular muscle invasion, and T2 longitudinal muscle invasion in ESCC ( p = 0.01).…”
Section: Discussionmentioning
confidence: 88%
“…23,24 Current evidence on the prognostic value of the T2 substage in ESCC is still scarce and limited to several studies involving small sample sizes. [6][7][8] The strength of our study included the level of evidence, which involved a multicenter, large sample size, and prospectively collected database. Furthermore, neoadjuvant therapy has become the standard treatment for locally advanced esophageal cancer.…”
Section: Survival and Depth Of Muscularis Propria Invasionmentioning
confidence: 99%
See 2 more Smart Citations